Technical Review: Analysis and Appraisal of Four-Dimensional Building Information Modeling Usability in Construction and Engineering Projects - Lopez, R.; Chong, Heap Yih; Wang, X.; Graham, J. (American Society of Civil Engineers, 2016)
Building information modeling (BIM) fundamentally requires the importation of a three-dimensional (3D) model with a series of repository data. Numerous studies have been conducted to clarify the philosophy of BIM and promote its adoption in construction and engineering projects. The primary contributions of this research to the construction engineering and management body of knowledge are the technical review, analysis, and appraisal of various issues concerning the usability of four-dimensional (4D) BIM. The research aims to determine the readiness and development of 4D BIM. A technical literature review was conducted of various BIM software websites, journal articles, brochures, and videos about required 4D elements. A comparative analysis was conducted to compare the technical (TECA) and project-planning functionality (PPFA) aspects of developing 4D models with features provided by available BIM software. This analysis yielded matrices that can be used to guide decision making on which BIM software to invest in. The results reveal that all of the software packages in their way serve the purpose of developing a 4D BIM model.